Status dan Ketersediaan Unsur Hara Mikro Seng (Zn) pada Lahan Sawah Berdasarkan Indeks Pertanaman: Status and Availability of Micronutrient Zinc (Zn) in Rice Fields based on Cropping Index - Nahumarury, Nurul Khalishah; Jayadi, Muh.; Laban, Sartika (Universitas Hasanuddin, 2025)
Zn is one of the essential micronutrients for rice plants. Increasing the Cropping Index (CI) to enhanced rice productivity, leads to increased Zn absorption. Without proper micronutrient fertilization, the soil can potentially be deficient in Zn. This study aims to study the differences in the status and availability of Zn micronutrients in paddy fields based on the Rice Cropping Index. The research was conducted in Tanete village, Simbang sub-district, Maros. Sample points were determined using purposive sampling method. There were eight sample points, namely two points each in CI300 rice fields with 10 years of application, CI300 with more than 10 years, CI200 with less than 30 years, and CI200 with more than 30 years of application. The parameters observed were texture, pH, C-organic, Zn-total, and Zn-available. Correlation analysis was conducted to see the relationship between soil properties. Zn availability ranged from 0.05 - 2.47 ppm. The availability of Zn in CI300 and CI200 rice fields is lower in those with a longer age of use. This is related to the length and intensity of land use, where more Zn nutrients are mined, resulting in reduced Zn availability in the soil. Available Zn increases with the increase of soil C-Organic and Zn-total. Zn availability is classified as low to high. Zn availability in CI300 rice fields with <10 years of use is higher than with >10 years of use. The availability of Zn in CI200 rice fields with <30 years of use is higher than that of >30 years of use. Zn availability has a strong positive correlation with Zn-total and soil C-Organic, and a moderate correlation with soil pH.